2015
DOI: 10.1021/acs.iecr.5b03445
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Modeling Study of the Adsorption Equilibrium and Dynamics of Water Vapor on Activated Carbon

Abstract: In this work, the adsorption of water vapor on a commercial activated carbon is studied by means of static and dynamic measurements. To this end, two customized setups are used, which are able to deal with the challenges associated with adsorption measurements under humid conditions. In the first part, the equilibrium of water vapor on activated carbon during adsorption and desorption at 45 °C is characterized. The equilibrium adsorbed amount of water vapor exhibits a pronounced hysteresis loop, requiring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 47 publications
1
60
0
Order By: Relevance
“…Although the adsorption equilibrium and mechanisms of water vapor adsorption on activated carbon have been widely investigated [16][17][18][19], very few studies have used fixed-bed experiments to gain insight into the adsorption dynamics of water vapor on activated carbon [20][21][22].The impact of water vapor on the capacity of biomass-based activated carbons to capture CO 2 has been evaluated: adsorption equilibrium data, measured for CO 2 , N 2 , O 2 and H 2 O, and breakthrough experiments performed under different relative humidity were conducted to explore the mutual influence of CO 2 and H 2 O adsorption.…”
mentioning
confidence: 99%
“…Although the adsorption equilibrium and mechanisms of water vapor adsorption on activated carbon have been widely investigated [16][17][18][19], very few studies have used fixed-bed experiments to gain insight into the adsorption dynamics of water vapor on activated carbon [20][21][22].The impact of water vapor on the capacity of biomass-based activated carbons to capture CO 2 has been evaluated: adsorption equilibrium data, measured for CO 2 , N 2 , O 2 and H 2 O, and breakthrough experiments performed under different relative humidity were conducted to explore the mutual influence of CO 2 and H 2 O adsorption.…”
mentioning
confidence: 99%
“…The fact that at higher flowrates the system is under kinetic control indicates that it is also possible to use the same instrument to measure kinetic properties, but the focus of this contribution is that of determining accurate equilibrium properties. It is important to note that the interpretation of kinetic experiments requires the knowledge of the derivative of the adsorption isotherm (Chmelik and Kärger, 2016;Glover et al, 2008;Hefti et al, 2015;Kärger et al, 2012;Lin et al, 1996;Ruthven, 1984) and clearly this can be estimated accurately from ZLC measurements given the large number of points available, particularly in the adsorption and desorption branches.…”
Section: Main Adsorption-desorption Curvesmentioning
confidence: 99%
“…Brunauer et al The models formulated by Rajniak et al [60] and Liu et al [54] have been used for the simulation of pressure swing adsorption processes in packed beds for water vapor removal [62][63][64][65]. Therefore, such models are probably considered the most appropriate analytical expressions for the correlation of type IV isotherms.…”
Section: Ref Model Expressionmentioning
confidence: 99%
“…Due to the large adsorbed phase concentration change when adsorbing a condensable vapor, the mass transfer coefficient is strongly dependent on the amount adsorbed. In many experimental studies [63], the mass transfer coefficient has shown a clear minimum located in the hysteresis region of the equilibrium isotherm. This phenomenon has been theoretically predicted considering different approaches.…”
Section: Kinetic Models 91 Introductionmentioning
confidence: 99%
See 1 more Smart Citation